The dynamics of chromatin states mediated by epigenetic modifications during somatic cell reprogramming - Peng, Jing; Zhang, Wen Jie; Zhang, Qi; Su, Ying Hua; Tang, Li Ping (Frontiers in Cell and Developmental Biology, 2023)
Somatic cell reprogramming (SCR) is the conversion of differentiated somatic cells into totipotent or pluripotent cells through a variety of methods. SCR also provides a platform to investigate the role of chromatin-based factors in establishing and maintaining totipotency or pluripotency, since high expression of totipotency- or pluripotency-related genes usually requires an active chromatin state. Several studies in plants or mammals have recently shed light on the molecular mechanisms by which epigenetic modifications regulate the expression of totipotency or pluripotency genes by altering their chromatin states. In this review, we present a comprehensive overview of the dynamic changes in epigenetic modifications and chromatin states during reprogramming from somatic cells to totipotent or pluripotent cells. In addition, we illustrate the potential role of DNA methylation, histone modifications, histone variants, and chromatin remodeling during SCR, which will pave the way to developing reliable strategies for efficient cellular reprogramming.